ANALISIS KEBUTUHAN UNTUK PENINGKATAN USAHA PETERNAKAN SAPI PERAH DI KECAMATAN UNGARAN TIMUR KABUPATEN SEMARANG - T. Dalmiyatun; W. Roessali; W. Sumekar; D. Mardiningsih (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
This research aimed to study the needs of members of farmers District East Ungaran  Semarang  Regency  for  the  development  of  their  farming.  This  research analyzed descriptively by using the approach of PRA  (Participatory Rural Appraisal) approach,  with  the  techniques  of  thematic  mapping,  trends  and  changes,  seasonal calendar,  daily  routine,  livelihood  analysis  and  Venn  Diagram  on  dairy  farmers.Results from the application of each single technique then was discussed in Focused Group  Discussion  (FGD)  attended  by  village  officers  and  extension  worker.  The results of the study can be contained in rank as follows: 1) The activities carried out by members of dairy farmer groups is still traditional. Technologies of seed selection,feed, milking, harvest and post-harvest has not been much progress, yet, 2) Limited knowledge and access to sources of technology, resources, and capital and programs for  both  private  and  government  3)  Limitation  of  production  facilities  and infrastructure,  which  resulted  in  small-scale  livestock  ownership  with  inadequate productivity,  and  4)  Limited  mastery  of  market  information,  both  for  sale  of  the products and purchase of the production factors.